Modelo de logística reversa: um estudo de caso em uma empresa do setor de telecomunicações - Sousa, Marcelo Jose de (2015)
The main purpose of this study is to analyze the reverse logistic model introduced by a telecommunication company in Brazil and the relationship with its supply chain as well as to present how this company had adjusted its operational model and the key processes aiming to obtain efficiency and economic balance in its reverse chain. The qualitative and quantitative research has based on information and internal data of the company, in the period of 2009 until 2014. It has verified the goals, performance indicators and processes implemented, intending to adjust them to the requirements of the Solid Waste Nacional Policy (PNRS). Finally, it was discussed the adopted model in implementing the Reverse Logistic Center, including the relationship with business partners, governance and results achieved. This model and its concept has spread for many other operations of the company and nowadays, is recognized a reference of operational excellence in managing reverse chains